Prospective Teachers’ Opinions of Reward, Punishment and Discrimination in Learning Environments - Hülya Pehlivan; Pınar Köseoğlu; Zeynep Şen (Elementary Education Online, 2023)
Classroom is the environment where students and teachers share the knowledge and experiences they possess and provide through various communication instruments so as to attain educational goals in an appropriate arrangement. Student-student and teacher-student interactions occur in the classroom, in which learning and teaching activities are actualised. Teachers responsible for planning and implementing classroom activities give rewards and punishment to students and make discrimination between them in the classroom environment, and students who are exposed to or follow these practices also make inferences about them. Therefore, this study sets out to reveal how often rewarding, punishment and discrimination practice is used in the classroom according to prospective teachers’ perceptions and what impacts the practice have on students. The study uses qualitative research method. The research was conducted with the participation of ten prospective teachers. The data were collected through focus group interviews. MAXQDA 11, a data analysis programme, was used in the analysis of the data, and following the analysis, interpretations were made on the data. The results obtained demonstrated that teachers resorted the most frequently to materialistic, psychological and social rewards; that they reward students’ academic behaviours more and that they most frequently gave physical, psychological and social punishment to students in prospective teachers’ views. Prospective teachers also thought that teachers made student discrimination for such reasons as individual properties, academic achievement, socio-economic levels and political views.